Migrations, families, generations: Language transmission among several Italian communities in England - Margherita Di Salvo (Anuac, 2015)
This paper researches the ethnic language shift in two Italian communities in the UK, those in Bedford and Cambridge. It focuses mainly on Italians of first and second generation. The present study questions whether the loss of the ethnic language (Italian or an Italian dialect), can be very costly to the migrants and their families and what happens in family in which adults do not understand children and children do not understand adults and how, in these dynamics, Italian identity remains.